Rethinking the Native American medicine wheel garden: from an outdoor classroom to celebration and land acknowledgement. (3rd July 2022) - Beasley, Todd
Abstract: The Native American Medicine Wheel is a powerful tool to bring alive curricular connections from science and history to mathematics and civics as part of schoolyard gardening initiatives. As a living lab these gardens also serve as valuable tools to reinforce lessons on habitat enhancement. However, deeper lessons connected to the cultures of Native Americans and land acknowledgement are embedded throughout and serve as a progressive investment to campus greening initiatives that raise awareness to contemporary social issues.